Effects of fly ash fineness, nano silica, and curing types on mechanical and durability properties of fly ash mortars - Arel, H.; Shaikh, Faiz (International Federation of Prestressing, 2018)
The effects of nano silica (NS), three different fly ash contents, two curing types and exposure to sulfate solution on mechanical and durability properties of two types of fly ash mortars are evaluated in this study. Results show that the wet-cured mortars containing finer fly ash exhibited higher compressive strength at all ages than that containing coarser fly ash. The addition of colloidal NS improved the compressive strength of both types of fly ash mortars at all ages with significant improvement at early ages. The effect of steam curing slightly improved the 3-day compressive strength of control cement mortar and both fly ash mortars with reduction starts from 7 days onwards. However, the addition of NS improved the compressive strengths at all ages of all fly ash concretes subjected to steam curing. The exposure to sulfate solution adversely affected the compressive strength at all ages of all fly ash concretes irrespective of fly ash contents, fineness types, and NS addition. Fly ash mortars containing finer fly ash exhibited slightly higher drying shrinkages but lower rate of water sorption than the mortars containing coarser fly ash. The addition of NS significantly increased the drying shrinkage and decreased the rate of water sorption of both types of fly ash mortars containing all fly ash contents.